Analysis Of Skywalkers English Lesson Marketing Strategy - Pratiwi, Feriska; Jeana Rachel, Angelika; Rachma Firdaus, Intan; Gustav Gloor, Hanzl (LPPM Universitas Duta Bangsa Surakarta, 2023)
This study aims to determine the application of Skywalkers English Lesson marketing strategy to find the right marketing strategy in the marketing mix, including 4P (product, price, promotion, place) at Skywalkers English Lesson tutoring institution to reach the target market. Using a descriptive qualitative approach, it can answer the problems that researchers have found and analyze the phenomena that occur in Primagama accompanied by SWOT Analysis to review the strengths and opportunities owned by the organization and then utilize as much as possible to reduce the weaknesses and threats